2020
DOI: 10.1080/21645515.2020.1804246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of refusal to vaccine in the neonatal period on the implementation of the vaccination calendar in the first year of life

Abstract: Introduction: The level of vaccination coverage with obligatory preparations in Poland reaches 98%. This is facilitated by the introduction of the Individual Vaccination Calendar (IVC) compliant with medical contraindications to vaccination. Aim: The aim of the study was to assess whether the refusal of vaccinations after birth has an impact on the proper implementation of the vaccination calendar in the first year of life. Methods: The study involved healthy, term newborns who were born in the Department of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Where the team agrees on what is going to be done and how it is going to be done [11]. The implementation is where the Sprint begins to develop, which will last between 1 to 4 weeks, and there will be daily meetings of 10 to 15 minutes where feedback is given on what has been done so far and what will continue to be done [4]. Also, Sprint review, is a meeting where the review of the project increment is made, where the client will evaluate what was done during the Sprint and indicate if there are any changes [12].…”
Section: Scrummentioning
confidence: 99%
See 1 more Smart Citation
“…Where the team agrees on what is going to be done and how it is going to be done [11]. The implementation is where the Sprint begins to develop, which will last between 1 to 4 weeks, and there will be daily meetings of 10 to 15 minutes where feedback is given on what has been done so far and what will continue to be done [4]. Also, Sprint review, is a meeting where the review of the project increment is made, where the client will evaluate what was done during the Sprint and indicate if there are any changes [12].…”
Section: Scrummentioning
confidence: 99%
“…On the other hand, before the pandemic there were 41% of children who did not receive the vaccine in their first year of life [3] and with the arrival of COVID-19, parents did not know how to act in this situation, and this is due to the lack of good guidance from health personnel. Since 46% of those surveyed indicated that they did not receive adequate information on what measures to take in the face of a pandemic in order to continue with the vaccination schedule [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, the content of professional training, such as medical and nursing education, is constantly undergoing innovation and change; therefore, improving the knowledge and decision-making abilities of students is a crucial goal in vocational education [ 1 ]. For example, caring for the health of newborns is even more challenging in the face of various infectious diseases, such as during the COVID-19 pandemic [ 2 , 3 ]. In particular, there are several challenges to neonatal vaccination in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, already before the pandemic there were 41% of children who did not receive the vaccine in their first year of life [3], and with the arrival of COVID-19, parents did not know how to act in this situation; This is due to the lack of good guidance from health personnel and 46% of parents indicated that they did not receive adequate information on what measures to take in the event of a pandemic, in order to continue immunizing their minors without risk of contagion. [2].…”
Section: Introductionmentioning
confidence: 99%